2019
DOI: 10.1002/2211-5463.12711
|View full text |Cite
|
Sign up to set email alerts
|

The HSP90/Akt pathway may mediate artemether‐induced apoptosis of Cal27 cells

Abstract: Tongue squamous cell carcinoma is the most common malignant tumor in oral and maxillofacial regions. Recent research has found that artemether can inhibit growth and induce apoptosis of cancer cells, although the mechanism is not clear. The present study aimed to explore the correlation between the HSP90/Akt pathway and artemether‐induced apoptosis of Cal27 cells. A cell counting kit‐8 and flow cytometry were used to detect the proliferation and apoptosis of Cal27 cells, respectively, mRNA expression was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Yamachika et al also reported that ART induces apoptosis in human gingival epithelial cells that have been immortalised and transformed by HPV 16 (Yamachika et al, 2004). Artemether, an ART derivative, has also been reported to induce apoptosis in a tongue squamous cell line (Cal27) via the HSP90/Akt pathway (Wu et al, 2019). However, in the present study, we were unable to distinguish the proportion of tumour volume reduction caused by angiogenesis inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Yamachika et al also reported that ART induces apoptosis in human gingival epithelial cells that have been immortalised and transformed by HPV 16 (Yamachika et al, 2004). Artemether, an ART derivative, has also been reported to induce apoptosis in a tongue squamous cell line (Cal27) via the HSP90/Akt pathway (Wu et al, 2019). However, in the present study, we were unable to distinguish the proportion of tumour volume reduction caused by angiogenesis inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…However, HSP90 inhibitor monotherapy failed to improve the survival of patients with lung cancer, suggesting that drug resistance also limits the efficacy [ 47 ]. HSP90 forms a complex with AKT and thus modulates AKT activity [ 48 ]. Consistently, we found that STA-9090 decreased the levels of AKT, p-AKT, and p-S6 in lung cancer cells ( Figure 4(k) ).…”
Section: Discussionmentioning
confidence: 99%
“…These results revealed that FER1L4 regulated the expression of PTEN protein and thus inhibited the expression of AKT phosphorylation. (17,18). We previously revealed that overexpressed FER1L4 regulated the PTEN protein and inhibited the phosphorylation of the AKT protein, which may also be related to apoptosis.…”
Section: Overexpression Of Lncrna Fer1l4 Inhibits the Invasion And Mi...mentioning
confidence: 99%